Les vacances annuelles dans l'arbitrage québécois des griefs - Lapointe, Catherine (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
This article is a treatment of the decisions of courts of arbitration principally in the province of Quebec, with respect to grievances and problems which occur in regulating the annual vacation of employees. There exists three main problem areas. The first consists of the determination of the duration of the annual vacation and necessitates a study of the definition of the « service » notion. The second, concerns the remuneration to which the employee is entitled for such holidays. And lastly, is the difficulty which occurs when there is a conflict between the employer and the employee as to the period during which the annual vacation may be taken.